Gold Nanomaterials: From Preparation to Pharmaceutical Design and Application - Rossi, Michele; Della Pina, Cristina; Falletta, Ermelinda (Current Pharmaceutical Design, 2016)
The present mini review offers a brief overview on the preparation and modification of gold nanomaterials (AuNMs) designed for biomedical applications, including biosensors, bioimaging, phototherapy and importantly gene/drug delivery. As biocompatibility is a prerequisite for safe pharmaceutical application, the potential risk of AuNMs to biological systems is also assessed.
Keywords: biomedical application